FACTORS RELATED WITH HOSPITAL INFORMATION SYSTEM (HIMS) POOR PERFORMANCE FROM USER’S EVALUATIONS THOROUGH MALCOLM BALDRIGE CONCEPT IN KERTHA USADA HOSPITAL SINGARAJA-BALI - I Wayan Parna Arianta (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Hospital is developing not only as social entity also for business. As business entity the hospital must gain the profit. To have profit the hospital must increase the productivity and keep the level of patients visit. The hospital should keep the patients and employees satisfaction, with the efficiency within. Use hospital information management system (HIMS) will be helping. HIMS must have good performance to make satisfy the users, either internal or external. Factors related are: strategic planning which is involve all of the stakeholders, practice and accompaniment while implementation, benefit for business process (quality control, integration, monitoring & evaluation, with full support from the hospital management. This study wants to see the entire factor by qualitative study associated with Malcom Baldrige Concept. Aims: This study is aimed to find out factors related with HIMS poor performance from Malcom Baldrige concept including leadership, strategic planning, focuses on patients-customer and markets, measurement-analyze and knowledge management, work-force focus, process management, and result. Methods: This study was done by a qualitative study to find out entire factors related with Kertha Usada HIMS poor performance thorough Malcom Baldrige Concept. Results: The key informant reveals the factors related with Kertha Usada HIMS poor performance are: difficult to operate, inadequate training and accompaniment, couldn’t integrated, didn’t gave benefit on works, no incentive, and less support from the management. Conclusion: The hospital should have good hospital governance in the used of Hospital Information Management System.